Sources And Levels Of Foreign Language Teaching Anxiety Among Pre-service And In-service Algerian Efl Teachers - Abdelbasset Dou; Abdelhalim Chouli (The Journal of Studies in Language, Culture and Society)
Foreign language teaching anxiety describes a teaching experience associated with fear, apprehension, uneasiness and/or worry. This research paper investigates EFL teachers’ anxiety in two different stages: pre-service teaching (training or practicum) and in-service teaching. Particularly, the paper attempts to check the relevant foreign language teaching anxiety sources and degrees among pre-service and in-service Algerian EFL teachers. The first group is fifth-year EFL student teachers at (1) Assia Djebar Training High School (ENS of Constantine) and (2) Sheikh Mubarak al-Mili Training High School (ENS of Bouzareah, Algiers), and the second group is new-in-service secondary school teachers working in different Algerian cities. The study initiates a causal-comparative investigation of anxiety among teachers in their teaching practicum and permanent secondary school teachers who have one year of teaching experience. One research tool is designed for both groups, a questionnaire that includes contextual differences for the periods and conditions of participants (either pre-service or in-service). The results indicated that the lack of confidence as well as teaching productive skills are the major anxiety-provokers in the teaching practicum, whereas teaching language skills and grammar in addition to insufficient class preparation are the major sources of anxiety among new in-service teachers. Besides, the high degrees of foreign language teaching anxiety seemed to be more apparent among permanent teachers than among student teachers.